(untitled) (Journal of Computational Mathematics, 2020)
This paper proposes a method to construct an G^3 cubic spline curve from any given open control polygon. For any two inner Bézier points on each edge of a control polygon, we can define each Bézier junction point such that the spline curve is G^2-continuous. Then by suitably choosing the inner Bézier points, we can construct a global G^3 spline curve. The curvature combs and curvature plots show the advantage of the G^3 cubic spline curve in contrast with the traditional C^2 cubic spline curve.